2005
DOI: 10.1519/1533-4287(2005)19[305:eoprdr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physiological Responses During Recovery Following Three Resistance Exercise Programs

Abstract: The present study was conducted to examine (a) whether there is an association between maximal oxygen uptake (Vo(2)max) and reduction in postexercise heart rate (HR) and blood lactate concentrations ([La]) following resistance exercise and (b) how intensity and Volume of resistance exercise affect postexercise Vo(2). Eleven regularly weight-trained males (20.8 +/- 1.3 years; 96.2 +/- 14.4 kg, 182.4 +/- 7.3 cm) underwent 4 sets of squat exercise on 3 separate occasions that differed in both exercise intensity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 12 publications
4
28
0
1
Order By: Relevance
“…The acute elevation in HR showed similar peak values to previous studies (Collins et al 1989;Kang et al 2005). The lack of signiWcant diVerences observed between 5REP and 10REP protocols may suggest that the higher intensity observed in 5REP was oVset by the higher volume in 10REP.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The acute elevation in HR showed similar peak values to previous studies (Collins et al 1989;Kang et al 2005). The lack of signiWcant diVerences observed between 5REP and 10REP protocols may suggest that the higher intensity observed in 5REP was oVset by the higher volume in 10REP.…”
Section: Discussionsupporting
confidence: 85%
“…Considering that the acute metabolic responses to resistance exercise have important ramiWcations for eliciting changes in body composition, further research is warranted quantifying the metabolic response to RI manipulation. In addition, most studies quantifying the metabolic responses to resistance exercise have only reported a mean exercise value (Byrd et al 1988;Scala et al 1987) or the immediate post-exercise value (Kang et al 2005); only one study has provided data obtained during »30% of the total sets completed ; and none have quantiWed the acute metabolic responses during each RI within the protocol. Therefore, the purpose of the present investigation was to thoroughly examine and quantify the acute metabolic responses and subsequent lifting performances of the bench press exercise to various RI lengths (e.g., 30 s, 1, 2, 3, 5 min).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lower lactate production rate at low load exercise, a workout at lower loads may yield a higher blood LA due to the longer time the exercise could be sustained and lactate could accumulate. This may be an explanation for the results of the present study and those presented by other investigations which measured significantly higher blood or plasma LA after exercise protocols at lower loads (Hunter et al 1988;Kang et al 2005;Mazzetti et al 2007). Consequently, when a higher glycolytic rate occurs due to a higher load a higher blood LA may result when exercise duration and/or total work are matched between exercise protocols of different external loads (Hunter et al 2003;Lagally et al 2002;Thornton and Potteiger 2002).…”
Section: Blood Lactatesupporting
confidence: 79%
“…Other studies reported significantly higher metabolic rates and/or a higher _ VO 2 due to an increased load (Beckham and Earnest 2000;Hunter et al 1988;Willoughby et al 1991). On the contrary, other studies reported a significantly higher _ VO 2 -response to a squat exercise with lower external load (Kang et al 2005;Mazzetti et al 2007). All these results are in contrast to the present findings and to those of other studies finding no differences in _ VO 2 -response between protocols of different loads (Kalb and Hunter 1991;Ratamess et al 2007; Thornton and Potteiger 2002).…”
Section: Oxygen Uptakementioning
confidence: 91%
See 1 more Smart Citation